2023
DOI: 10.2298/vsp211126026k
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal self-injury in a clinical sample of adolescents in Serbia

Abstract: Background / Aim. Non-suicidal self-injury (NSSI) among adolescents is recognized as a significant public health concern. Adolescents with mental health problems are at especially high risk of NSSI. This research aimed to investigate possible differences in gender, age, emotional reactivity, and expression of psychopathological characteristics between two groups of adolescents within a clinical population where the main distinguishing factor was the presence/absence of NSSI. Methods. The obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(64 reference statements)
3
0
0
Order By: Relevance
“…Regarding the descriptive and contextual characteristics of NSSI, the findings of the present study are consistent with findings in related literature in many aspects, including the age of onset of self-injury [2], the most common methods of NSSI [8,[23][24][25], the most affected body parts [24], the predominantly distressing urge to self-injure [26], the "impulsive" quality of self-injury in terms of the time that elapses between the thought of self-injury and the performance of the act [24,27], the experience of physical pain during self-injury [24], more of those who self-injure following stressful situations, where failure is considered an overwhelming situation [24], more participants who disclose their self-injurious behavior to others [28], more of participants who engage in substitute acts to avoid self-injury [24]. Although the existing literature on social influence in NSSI talks about contagion or the "spread" of NSSI behavior and reports from one person to another, and that people who have disclosed NSSI (either to adults or peers) are more likely to have friends who selfinjure [28], the majority of participants reported that the initial idea to self-injure was their idea.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the descriptive and contextual characteristics of NSSI, the findings of the present study are consistent with findings in related literature in many aspects, including the age of onset of self-injury [2], the most common methods of NSSI [8,[23][24][25], the most affected body parts [24], the predominantly distressing urge to self-injure [26], the "impulsive" quality of self-injury in terms of the time that elapses between the thought of self-injury and the performance of the act [24,27], the experience of physical pain during self-injury [24], more of those who self-injure following stressful situations, where failure is considered an overwhelming situation [24], more participants who disclose their self-injurious behavior to others [28], more of participants who engage in substitute acts to avoid self-injury [24]. Although the existing literature on social influence in NSSI talks about contagion or the "spread" of NSSI behavior and reports from one person to another, and that people who have disclosed NSSI (either to adults or peers) are more likely to have friends who selfinjure [28], the majority of participants reported that the initial idea to self-injure was their idea.…”
Section: Discussionsupporting
confidence: 90%
“…Although the existing literature on social influence in NSSI talks about contagion or the "spread" of NSSI behavior and reports from one person to another, and that people who have disclosed NSSI (either to adults or peers) are more likely to have friends who selfinjure [28], the majority of participants reported that the initial idea to self-injure was their idea. In terms of treatment for NSSI, a similar finding has been reported by other studies in our region, given the higher percentage of adolescents who reported that they had no treatment for NSSI [23,29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation